Human Hsp70 disaggregase reverses Parkinson’s-linked α-synuclein amyloid fibrils - Gao, Xuechao; Nussbaum-Krammer, Carmen; Mogk, Axel; Nillegoda, Nadinath B.; Mayer, Matthias P.; Bukau, Bernd (Molecular cell, 2015)
Intracellular amyloid fibrils linked to neurodegenerative disease typically accumulate in an age-related manner, suggesting inherent cellular capacity for counteracting amyloid formation in early life. Metazoan molecular chaperones assist native folding and block polymerization of amyloidogenic proteins, preempting amyloid fibril formation. Chaperone capacity for amyloid disassembly, however, is unclear. Here, we show that a specific combination of human Hsp70 disaggregase-associated chaperone components efficiently disassembles α-synuclein amyloid fibrils characteristic of Parkinson’s disease in vitro. Specifically, the Hsc70 chaperone, the class B J-protein DNAJB1, and an Hsp110 family nucleotide exchange factor (NEF) provide ATP-dependent activity that disassembles amyloids within minutes via combined fibril fragmentation and depolymerization. This ultimately generates non-toxic α-synuclein monomers. Concerted, rapid interaction cycles of all three chaperone components with fibrils generate the power stroke required for disassembly. This identifies a powerful human Hsp70 disaggregase activity that efficiently disassembles amyloid fibrils and points to crucial yet undefined biology underlying amyloid-based diseases.